Self-repairing high-energy-storage ice-snow-resistant double-layer composite microcapsule suitable for asphalt surface layer and preparation method and application thereof
By using a double-layer composite microcapsule structure on the asphalt pavement, combined with the design of phase change microcapsules and self-healing microcapsules, the problems of poor self-repairing effect and low thermal conductivity of phase change materials in the prior art are solved, and the efficient self-repairing and high energy storage and anti-ice of ice and snow on the asphalt pavement in low temperature environments are achieved.
Patent Information
- Application Number
- CN202411948354.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-12-27
AI Technical Summary
The self-repair microcapsules used in existing asphalt pavement have problems such as poor core material release effect, unstable shell wall material, poor self-repair effect, and low thermal conductivity, easy leakage and single function in asphalt pavement applications.
A double-layer composite microcapsule structure is adopted, in which the inner layer is a phase-change microcapsule core composed of n-octanoic acid, tetradecane and sodium polyacrylate emulsifier, and a phase-change microcapsule shell composed of carbon nanotubes and bipolymers, and the outer layer is a self-healing microcapsule core and shell composed of bio-oil, carbon nanotubes and bipolymers. This structure improves energy storage and thermal stability through the use of carbon nanotubes, and improves the strength and chemical stability of the material through bipolymers.
It realizes efficient self-repair and high energy storage effects of asphalt pavement in low temperature environments, improves the ice and snow resistance of asphalt materials, extends the service life of asphalt pavement, and solves the problems of low thermal conductivity and easy leakage of traditional phase change materials.
Smart Images

Figure CN119751982A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of microcapsule preparation, and belongs to the field of self-repairing high-energy storage anti-icing / deicing asphalt preparation. Background Art
[0002] During the winter service of asphalt pavement, it is inevitably affected by the low temperature environment, resulting in low-temperature cracking and other defects. Asphalt, as a viscoelastic material, has a certain self-healing ability. However, the self-healing process of asphalt is complex and slow, and asphalt pavement does not have sufficient self-healing time during normal service. Therefore, improving the self-healing ability of asphalt and shortening its self-healing time are important for improving the durability of asphalt pavement. Among them, self-healing microcapsule technology is known as one of the effective methods to improve the self-healing ability of asphalt materials due to its durability and long-term effects. At the same time, phase change material is a latent heat storage material with great potential in road engineering applications, which can effectively improve road defects such as rutting, deformation, and frost cracking of asphalt pavements under high and low temperature conditions.
[0003] The self-healing microcapsules currently used in asphalt pavement have problems such as poor core material release and self-healing effects, unstable shell wall materials, and poor self-healing effects. At the same time, traditional solid-liquid phase change materials have disadvantages such as low thermal conductivity, easy leakage, and single application function during application, which greatly limits their practical application in energy conversion and storage. Summary of the invention
[0004] The present invention aims to solve the technical problems of poor core material release effect, unstable shell wall material, poor self-repair effect, and low thermal conductivity, easy leakage, and single application function of traditional solid-liquid phase change materials in the process of asphalt pavement application. The present invention provides a double-layer composite microcapsule suitable for asphalt surface layer, which has the advantages of self-repair, high energy storage and ice and snow resistance, as well as its preparation method and application.
[0005] The double-layer composite microcapsule with self-repairing, high energy storage and ice and snow resistance suitable for asphalt surface layer of the present invention is composed of an inner phase change microcapsule core, an inner phase change microcapsule shell, an outer self-repairing microcapsule core and an outer self-repairing microcapsule shell from the inside to the outside;
[0006] The core of the internal phase-change microcapsule is a mixture of octanoic acid, tetradecane, sodium polyacrylate emulsifier and deionized water. Octanoic acid and tetradecane change from liquid to solid under low temperature conditions. This process releases heat, slows down the cooling rate of the pavement asphalt, regulates the low temperature environment of the road project, and thus improves the low-temperature crack resistance of the asphalt binder.
[0007] The inner phase change microcapsule shell is made of a mixture of carbon nanotubes, dual polymers and deionized water; the dual polymers are made of polyvinyl alcohol and methylated hexamethylol melamine resin. The carbon nanotubes are entangled with the dual polymers and deposited in the inner shell wall. The dual polymers as inner shell materials can improve the strength and chemical stability of the phase change microcapsules; carbon nanotubes as photothermal materials can convert light energy into heat energy to improve the energy storage effect of the phase change material. At the same time, carbon nanotubes generate heat energy under the action of external electric or magnetic fields to further improve the energy storage of the phase change material.
[0008] The core of the external self-healing microcapsule is a mixture of bio-oil, carbon nanotubes, styrene maleic anhydride emulsifier, polyether F127 surfactant and deionized water; among them, carbon nanotubes increase the filling effect of bio-oil on cracks and pores in asphalt pavement, improve the permeability and repairability of bio-oil, and thus improve the self-healing performance of asphalt materials.
[0009] The shell of the external self-repairing microcapsule is made of a mixture of carbon nanotubes, a double polymer and deionized water; wherein the double polymer is prepared from polyvinyl alcohol and methylated hexahydroxymethyl melamine resin; the carbon nanotubes and the double polymer are entangled and deposited in the shell wall, and the double polymer as a shell material can improve the responsiveness of the self-repairing microcapsule to the external environment; polyvinyl alcohol, as a vulnerable part of the shell material of the external self-repairing microcapsule, is more susceptible to damage and can accelerate the release of the core material; methylated hexahydroxymethyl melamine resin has the advantages of high stability and harmlessness due to its high cross-linking density and low formaldehyde content; carbon nanotubes give the external self-repairing microcapsule a dual mechanism of thermal induction and self-healing, which enhances the damage resistance of the shell material and the release effect of the core material. At the same time, the thermal induction of carbon nanotubes can also improve the self-healing ability of the asphalt material.
[0010] The preparation method of the above-mentioned double-layer composite microcapsules with self-repairing, high energy storage and ice and snow resistance suitable for asphalt surface layer is carried out according to the following steps:
[0011] 1. Preparation of internal phase change microcapsule core solution: Weigh sodium polyacrylate emulsifier, octanoic acid, tetradecane and deionized water in a mass ratio of 1: (95-100): (95-100): (190-210) respectively; first mix octanoic acid and tetradecane, then add them into deionized water and mix evenly, and heat until the raw materials are completely dissolved to obtain a mixed solution; then adjust the pH value of the mixed solution to 3.5-4.5 with 1-1.5 mol / L citric acid; finally, add sodium polyacrylate emulsifier to the mixed solution, stir for 20-40 min at a temperature of 65-75° C. for emulsification, and obtain a uniform and stable internal phase change microcapsule core solution;
[0012] 2. Preparation of internal phase change microcapsule shell solution: Weigh polyvinyl alcohol, methyl etherified hexahydroxymethyl melamine resin, carbon nanotubes and deionized water according to the mass ratio of 1: (65-70): (1.2-1.5): (140-155); add polyvinyl alcohol to deionized water and mix well, then add methyl etherified hexahydroxymethyl melamine resin and mix well to obtain a mixed solution; adjust the pH value of the mixed solution to 7.5-8.5 with sodium hydroxide solution, and then stir for 20-40 minutes at a temperature of 65-75°C and a stirring speed of 500-700 r / min; finally, add carbon nanotubes to the mixed solution, and treat it ultrasonically to entangle it with the double polymer and mix well to obtain an internal phase change microcapsule shell solution;
[0013] 3. Preparation of internal high energy storage phase change microcapsules: drip the internal phase change microcapsule shell solution into the internal phase change microcapsule core solution, and adjust the solution pH to 3.5-4.5 with citric acid; after dripping the internal phase change microcapsule shell solution, stir at a temperature of 65-75°C and a stirring speed of 1000-1500r / min for 60-90min to allow the inner wall material to undergo a cross-linking and curing reaction on the surface of the core material, and stop stirring after the solution temperature is naturally cooled to room temperature; then filter the reaction solution, wash with anhydrous ethanol, and vacuum dry to obtain internal high energy storage phase change microcapsules;
[0014] 4. Preparation of external self-healing microcapsule core solution: Weigh 15-20 g / L of polyether F127 surfactant, carbon nanotubes, styrene maleic anhydride emulsifier, bio-oil and deionized water respectively according to the mass ratio of 1: (1.5-2): (2-3): (85-95): (185-200); first swell the styrene maleic anhydride emulsifier in deionized water for 20-24 h, heat the expanded styrene maleic anhydride solution to 45-55 ° C, and then add sodium hydroxide solution to adjust the pH of the solution to 9.5-10.5; then add bio-oil, carbon nanotubes and polyether F127 surfactant to the styrene maleic anhydride solution, stir with a high-speed shearing machine at a stirring speed of 500-700 r / min for 25-35 min to obtain a stable and uniform external self-healing microcapsule core solution;
[0015] 5. Preparation of external self-healing microcapsule shell solution: Weigh polyvinyl alcohol, methyl etherified hexahydroxymethyl melamine resin, carbon nanotubes and deionized water according to the mass ratio of 1: (65-70): (1.2-1.5): (140-155); stir the polyvinyl alcohol and deionized water evenly, and add them to the methyl etherified hexahydroxymethyl melamine resin, stir evenly to obtain a mixed solution; adjust the pH value of the mixed solution to 7.5-8.5 with sodium hydroxide solution; stir at a temperature of 65-75°C and a stirring speed of 500-700 r / min for 20-40 minutes; finally, add carbon nanotubes, and treat them ultrasonically to entangle and mix them with the double polymer to obtain an external microcapsule shell solution;
[0016] 6. Preparation of double-layer composite microcapsules: Add the inner high energy storage phase change microcapsules to the outer self-repairing microcapsule core solution at a temperature of 20-30°C, and then add them drop by drop to the outer self-repairing microcapsule shell solution. The outer self-repairing microcapsule core material containing the inner high energy storage phase change microcapsules attracts the outer wall material to the surrounding area through electrostatic adsorption; after the outer self-repairing microcapsule shell solution is added, the temperature is increased at a rate of 1-5°C / min. When the solution temperature rises to 65°C, citric acid is added to adjust the solution pH value to 4-5, and the temperature is continued to be increased at a rate of 1-5°C / min until the solution temperature reaches 80°C and stirred at this temperature at a stirring speed of 1000-1500r / min for 60-90min. The outer wall material undergoes cross-linking and curing reaction on the surface of the core material through mechanical stirring, and the solution temperature is naturally cooled to room temperature and stirring is stopped; finally, the reaction solution is filtered, washed with anhydrous ethanol, and vacuum dried to obtain a double-layer composite microcapsule suitable for asphalt surface layer with self-repairing, high energy storage and ice and snow resistance.
[0017] Furthermore, the ultrasonic treatment in step 2 is performed using a cell crusher, with an ultrasonic power of 85 to 95 W, an amplitude of 50% to 60%, and a time of 60 to 90 min.
[0018] Furthermore, in step three, the mass ratio of the internal phase change microcapsule shell solution to the internal phase change microcapsule core solution is 1:(1.4-1.6).
[0019] Furthermore, the concentration of the citric acid solution in step 3 and step 6 is 1-1.5 mol / L.
[0020] Furthermore, the vacuum drying in step three is carried out in a vacuum drying oven at a temperature of 20 to 30° C. for 20 to 24 hours.
[0021] Furthermore, the concentration of the sodium hydroxide solution in step 2, step 4 and step 5 is 1-2 mol / L.
[0022] Furthermore, the ultrasonic treatment in step five is performed using a cell disruptor, and the ultrasonic power is 85-95 W, the amplitude is 50%-60%, and the time is 60-90 min.
[0023] Furthermore, the mass ratio of the external self-repairing microcapsule shell solution to the external self-repairing microcapsule core solution in step six is 1:(1.4-1.6).
[0024] Furthermore, the vacuum drying in step six is carried out in a vacuum drying oven at a temperature of 20 to 30° C. for 20 to 24 hours.
[0025] The application of the above-mentioned double-layer composite microcapsules with self-repairing, high energy storage and ice and snow resistance suitable for asphalt surface layer is to use the double-layer composite microcapsules to prepare the surface layer of asphalt pavement. The specific method is: add the double-layer composite microcapsules with self-repairing, high energy storage and ice and snow resistance suitable for asphalt surface layer to the asphalt in a molten state, stir for 30 to 45 minutes under the condition of a stirring speed of 200 to 300 r / min of the mechanical device; finally, keep it at the melting temperature of asphalt for 10 to 15 minutes to obtain the road surface layer asphalt prepared by the double-layer composite microcapsules. Among them, the added mass of the double-layer composite microcapsules is 3% to 5% of the mass of the asphalt.
[0026] The double-layer composite microcapsules suitable for asphalt surface layers of the present invention and having both self-repairing, high energy storage and ice and snow resistance are composed of inner high energy storage phase change microcapsules and outer self-repairing microcapsules, specifically including an inner microcapsule core structure composed of energy storage phase change materials, an inner microcapsule shell structure composed of polymers doped with carbon-based photothermal materials, an outer microcapsule core structure composed of bio-oil-based repair agents, and an outer microcapsule shell structure composed of polymers doped with nanoparticles.
[0027] The present invention adopts an in-situ polymerization method to prepare double-layer composite microcapsules, specifically: firstly prepare an inner high energy storage phase change microcapsule; then prepare an outer microcapsule core structure and an outer microcapsule shell structure; finally, mix the inner high energy storage phase change microcapsule and the outer microcapsule core structure, and slowly add the outer microcapsule shell structure to form a double-layer composite microcapsule.
[0028] Compared with the prior art, the present invention breaks through the defects of the single function of traditional microcapsule composite materials and realizes the multifunctionality of self-repair, high energy storage and long-term anti-ice and snow. The double-layer composite microcapsules with self-repair, high energy storage and anti-ice and snow prepared by the present invention and suitable for the asphalt surface layer can not only achieve a high survival rate of microcapsules and a high healing and repair rate of cracks in asphalt pavement, but also have the advantages of high encapsulation rate of phase change materials, high thermal conductivity, good sealing performance, good thermal stability and good mechanical properties. The heat and high energy storage generated will increase the temperature of the asphalt material, melt the ice and snow on the asphalt pavement and inhibit the formation of ice layers, and finally realize the mechanism of self-repair, high energy storage and long-term anti-ice and snow. Compared with ordinary 70# matrix asphalt, the asphalt prepared by the double-layer composite microcapsules of the present invention has an improvement of 8.1% to 26.3% in healing index, 6.5% to 17.5% in needle penetration at 25°C, 1.9% to 8.4% in softening point and 12.2% to 23.6% in ductility.
[0029] In order to improve the performance of self-repairing microcapsules and enhance their application in asphalt, the present invention selects suitable materials from the microcapsule shell wall and core material to form self-repairing microcapsules with different structures and functions. In addition, in order to better utilize solar energy, the photothermal conversion and storage technology based on photothermal composite phase change materials is an effective method to convert solar energy into thermal energy and store it. At the same time, in order to ensure the balance between the thermal management requirements, mechanical strength and environmental load of asphalt pavement, microcapsule phase change materials are introduced. These microcapsule phase change materials can actively adjust the temperature of the asphalt pavement, thereby reducing temperature-related damage.
[0030] The road surface layer asphalt prepared by using the self-repairing, high energy storage and ice and snow resistant double-layer composite microcapsules suitable for asphalt surface layer of the present invention has an action process divided into two stages that are carried out in sequence, such as Figure 2 shown.
[0031] The first stage: Under the concentrated stress caused by the expansion of cracks in the asphalt pavement, its outer shell structure is destroyed, and the repair agent contained in the outer core is released and fills the crack defects. At the same time, the conductive nanomaterials contained in the outer shell structure will generate heat energy under the action of the external electric field or magnetic field, increase the fluidity of the core material, soften the asphalt around the self-healing microcapsules, improve the mixing degree of the core material and the asphalt material, promote the self-repair ability of asphalt cracks in the pavement, and achieve the purpose of extending the service life of the asphalt pavement and ensuring its normal service function.
[0032] The second stage: The repair agent that fills the cracks contains undamaged high-energy storage phase change microcapsules. After the composite microcapsule shell and outer core structure realize thermal induction and self-repair functions, the high-energy storage phase change microcapsules at the cracks continue to play a high energy storage role. The photothermal material contained in the wall of the high-energy storage phase change microcapsule not only stores light and heat in the phase change material, but also generates heat energy under the action of external electric or magnetic fields and then stores it in the phase change material, jointly realizing comprehensive properties such as high heat storage capacity, excellent light-to-heat conversion performance and good thermal conductivity, realizing the temperature regulation function of asphalt pavement in low temperature environment, and then solving the problem of cracking of asphalt binder of pavement under low temperature conditions in winter and effectively inhibiting the formation of ice on the surface layer of asphalt pavement. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 This is a schematic structural diagram of the double-layer composite microcapsule of the present invention which is suitable for asphalt surface layer and has both self-repairing, high energy storage and ice and snow resistance; 1 is the inner phase change microcapsule core, 2 is the inner phase change microcapsule shell; 3 is the outer self-repairing microcapsule core, and 4 is the outer self-repairing microcapsule shell.
[0034] Figure 2 This is a schematic diagram of the two stages of action of highway surface layer asphalt made of double-layer composite microcapsules that are suitable for asphalt surface layers and have both self-repairing, high energy storage and ice and snow resistance. DETAILED DESCRIPTION
[0035] The beneficial effects of the present invention are verified by the following examples.
[0036] Example 1: The preparation method of the double-layer composite microcapsules with self-repairing, high energy storage and ice and snow resistance suitable for asphalt surface layer of this embodiment is carried out according to the following steps:
[0037] 1. Preparation of internal phase change microcapsule core solution:
[0038] Sodium polyacrylate emulsifier, octanoic acid, tetradecane and deionized water are weighed respectively according to the mass ratio of 1:95:95:190;
[0039] Add n-octanoic acid and tetradecane into deionized water and mix them evenly, and heat until the raw materials are completely dissolved to obtain a mixed solution; then adjust the pH value of the mixed solution to 4 with 1 mol / L citric acid; then add sodium polyacrylate emulsifier into the mixed solution, stir for 30 minutes at a temperature of 70°C for emulsification, and obtain a uniform and stable internal phase change microcapsule core solution;
[0040] 2. Preparation of internal phase change microcapsule shell solution:
[0041] Polyvinyl alcohol, methyl etherified hexamethylol melamine resin, carbon nanotubes and deionized water are weighed according to the mass ratio of polyvinyl alcohol, methyl etherified hexamethylol melamine resin, carbon nanotubes and deionized water of 1:65:1.2:140;
[0042] After adding polyvinyl alcohol to deionized water and mixing evenly, methylated hexahydroxymethyl melamine resin is added and mixed evenly to obtain a mixed solution; the pH value of the mixed solution is adjusted to 8 with a 1.5 mol / L sodium hydroxide solution, and then stirred for 30 minutes at a temperature of 70°C and a stirring speed of 600 r / min; finally, carbon nanotubes are added to the mixed solution, and ultrasonically treated for 70 minutes using a cell crusher at an ultrasonic power of 90 W and an amplitude of 50%, so that the carbon nanotubes are entangled with the double polymer and deposited in the inner shell wall, thereby obtaining an inner phase change microcapsule shell solution;
[0043] 3. Preparation of internal high energy storage phase change microcapsules:
[0044] The inner phase change microcapsule shell solution was added dropwise to the inner phase change microcapsule core solution according to the mass ratio of the inner phase change microcapsule shell solution to the inner phase change microcapsule core solution of 1:1.5, and citric acid with a concentration of 1 mol / L was added to adjust the solution pH to 4; after the inner phase change microcapsule shell solution was added dropwise, stirring was performed at a temperature of 70°C and a stirring speed of 1000 r / min for 70 minutes to allow the inner wall material to undergo a cross-linking and curing reaction on the surface of the core material, and stirring was stopped after the solution temperature naturally cooled to room temperature; the reaction solution was then filtered, washed with anhydrous ethanol, and dried in a vacuum drying oven at a temperature of 25°C for 24 hours to obtain an inner high energy storage phase change microcapsule;
[0045] 4. Preparation of external self-repairing microcapsule core solution:
[0046] According to the mass ratio of polyether F127 surfactant, carbon nanotubes, styrene maleic anhydride emulsifier, bio-oil and deionized water of 1:1.5:2:85:185, 15 g / L of polyether F127 surfactant, carbon nanotubes, styrene maleic anhydride emulsifier, bio-oil and deionized water were taken respectively;
[0047] First, the styrene maleic anhydride emulsifier was swollen in deionized water for 24 hours, and the expanded styrene maleic anhydride solution was heated to 50°C, and then a 1.5 mol / L sodium hydroxide solution was added to adjust the pH of the solution to 10; and then a high-speed shearing machine was used to stir at a stirring speed of 600 r / min for 30 minutes to obtain a stable and uniform external self-healing microcapsule core solution;
[0048] 5. Preparation of external self-repairing microcapsule shell solution:
[0049] Polyvinyl alcohol, methyl etherified hexamethylol melamine resin, carbon nanotubes and deionized water are weighed respectively according to the mass ratio of polyvinyl alcohol, methyl etherified hexamethylol melamine resin, carbon nanotubes and deionized water being 1:65:1.2:140;
[0050] The polyvinyl alcohol and deionized water were stirred evenly, and then added into the methylated hexahydroxymethyl melamine resin, and stirred evenly to obtain a mixed solution; the pH value of the mixed solution was adjusted to 8 with a 1.5 mol / L sodium hydroxide solution; and then stirred at a stirring speed of 600 r / min for 30 minutes at a temperature of 70°C; and then carbon nanotubes were added, and a cell crusher was used to perform ultrasonic treatment for 70 minutes at an ultrasonic power of 90 W and an amplitude of 50%, so that the carbon nanotubes were entangled with the double polymer and deposited in the shell wall, and an external self-repairing microcapsule shell solution was obtained;
[0051] VI. Preparation of double-layer composite microcapsules
[0052] According to the mass ratio of the external self-repairing microcapsule shell solution to the external self-repairing microcapsule core solution of 1:1.5, the internal high energy storage phase change microcapsules were first added to the external self-repairing microcapsule core solution at a temperature of 25°C, and then added dropwise to the external self-repairing microcapsule shell solution. The external self-repairing microcapsule core material containing the internal high energy storage phase change microcapsules attracted the outer wall material to the surrounding by electrostatic adsorption. After the external self-repairing microcapsule shell solution was added, the temperature was increased at a rate of 2°C / min. When the solution temperature reached 65°C, 1 mol / L citric acid solution was added to The pH value of the solution was adjusted to 4, and the temperature was continued to rise at a rate of 2°C / min until the solution temperature reached 80°C and stirred at a stirring speed of 1000r / min for 60min. The outer wall material was cross-linked and cured on the surface of the core material through mechanical stirring. The solution temperature was naturally cooled to room temperature and stirring was stopped. Finally, the reaction solution was filtered, washed with anhydrous ethanol, and vacuum dried at 25°C for 24 hours to obtain a double-layer composite microcapsule suitable for asphalt surface layer with self-repairing, high energy storage and ice and snow resistance.
[0053] Comparative Example 1: This comparative example is to prepare a single self-repairing microcapsule, and the specific steps are as follows:
[0054] 1. Preparation of self-repairing microcapsule core solution:
[0055] According to the mass ratio of polyether F127 surfactant, carbon nanotubes, styrene maleic anhydride emulsifier, bio-oil and deionized water of 1:1.5:2:85:185, 15 g / L of polyether F127 surfactant, carbon nanotubes, styrene maleic anhydride emulsifier, bio-oil and deionized water were taken respectively;
[0056] First, the styrene maleic anhydride emulsifier was swollen in deionized water for 24 hours, and the expanded styrene maleic anhydride solution was heated to 50°C, and then 1.5 mol / L sodium hydroxide solution was added to adjust the pH of the solution to 10; then bio-oil, carbon nanotubes, and polyether F127 surfactant were added to the styrene maleic anhydride solution, and then a high-speed shearing machine was used to stir at a stirring speed of 600 r / min for 30 minutes to obtain a stable and uniform self-healing microcapsule core solution;
[0057] 2. Preparation of self-repairing microcapsule shell solution:
[0058] Polyvinyl alcohol, methyl etherified hexamethylol melamine resin, carbon nanotubes and deionized water are weighed respectively according to the mass ratio of polyvinyl alcohol, methyl etherified hexamethylol melamine resin, carbon nanotubes and deionized water being 1:65:1.2:140;
[0059] The polyvinyl alcohol and deionized water were stirred evenly, and then added into the methylated hexahydroxymethyl melamine resin, and stirred evenly to obtain a mixed solution; the pH value of the mixed solution was adjusted to 8 with a 1.5 mol / L sodium hydroxide solution; and then stirred at a stirring speed of 600 r / min for 30 minutes at a temperature of 70°C; and then carbon nanotubes were added, and a cell crusher was used to perform ultrasonic treatment for 70 minutes at an ultrasonic power of 90 W and an amplitude of 50%, so that the carbon nanotubes were entangled with the double polymer and deposited in the shell wall, and a self-repairing microcapsule shell solution was obtained;
[0060] 3. Preparation of self-repairing microcapsules:
[0061] According to the mass ratio of self-repairing microcapsule shell solution to self-repairing microcapsule core solution of 1:1.5, the self-repairing microcapsule core solution was added dropwise to the self-repairing microcapsule shell solution. After the self-repairing microcapsule shell solution was added, the temperature was increased at a rate of 2°C / min. When the solution temperature reached 65°C, 1 mol / L citric acid solution was added to adjust the solution pH value to 4. The temperature was continued to be increased at a rate of 2°C / min until the solution temperature reached 80°C and stirred at a stirring speed of 1000r / min for 60min. The outer wall material was cross-linked and cured on the surface of the core material through mechanical stirring. The solution temperature was naturally cooled to room temperature and stirring was stopped. Finally, the reaction solution was filtered, washed with anhydrous ethanol, and vacuum dried at 25°C for 24 hours to obtain a single self-repairing microcapsule.
[0062] The performance of the double-layer composite microcapsules prepared in Example 1 and the single self-healing microcapsules prepared in Comparative Example 1 were evaluated.
[0063] Firstly, the double-layer composite microcapsules prepared in Example 1 and the single self-healing microcapsules prepared in Comparative Example 1 were tested for their impermeability and thermal stability. The single self-healing microcapsules and the double-layer composite microcapsules were immersed in the same volume of ethanol solvent, respectively. After immersion for the same time, the mass loss rate of the core of the two microcapsules before and after immersion was tested to evaluate their impermeability.
[0064] The thermal stability of single self-healing microcapsules and double-layer composite microcapsules was analyzed by thermogravimetric analyzer at temperatures of 230-300°C, and their mass loss rate was used as an evaluation indicator.
[0065] The exothermic enthalpy of single phase change microcapsules and double-layer composite microcapsules was tested by differential scanning calorimetry.
[0066] The yield stress of single phase change microcapsules and double-layer composite microcapsules was tested by nanoindentation tester. In the nanoindentation test, the force was set to 50nN, maintained for 10s, and the displacement resolution was 0.01nm. The yield stress values of single phase change microcapsules and double-layer composite microcapsules at pH 5.0 were calculated based on the obtained load-displacement curves.
[0067] The test results are listed in Table 1.
[0068] Table 1 Performance comparison of the single phase change microcapsule of comparative example 1 and the double-layer composite microcapsule of embodiment 1
[0069]
[0070] Compared with the single self-repairing microcapsule of Comparative Example 1, the double-layer composite microcapsule of Example 1 has stronger impermeability and thermal stability, indicating that it is more stable and more conducive to the realization of the self-repairing function of the microcapsule. Compared with the single phase change microcapsule, the double-layer composite microcapsule has a larger yield stress and a larger exothermic enthalpy value, indicating that the double-layer composite microcapsule has better mechanical properties and can better adjust the low-temperature environment of the asphalt pavement, thereby improving the low-temperature crack resistance of the asphalt.
[0071] The double-layer composite microcapsules prepared in Example 1 are used to prepare asphalt for the surface layer of a highway. The specific method is as follows: the mass percentage of the double-layer composite microcapsules with self-repairing, high energy storage and ice and snow resistance suitable for the surface layer of asphalt prepared in Example 1 is 3%, 4% and 5% of the mass of asphalt, and the double-layer composite microcapsules with self-repairing, high energy storage and ice and snow resistance suitable for the surface layer of asphalt are added to the asphalt in a molten state, and stirred for 30 minutes under the condition that the stirring speed of the mechanical device is 300r / min; finally, it is kept at the melting temperature of asphalt for 10 minutes to obtain the surface layer of a highway asphalt containing the double-layer composite microcapsules.
[0072] First, the self-healing property of the road surface layer asphalt containing double-layer composite microcapsules was tested, and the self-healing property of the double-layer composite microcapsule asphalt with different dosages (0%, 3%, 4%, and 5%) was analyzed based on multiple intermittent fatigue tests of DSR. The test temperature of the multiple intermittent fatigue tests was 25°C, the loading strain was 3.0%, the loading frequency was 10Hz, the loading cycle was 10 cycles, and the intermittent time was 0s and 3s, respectively. When the modulus dropped to 50% of the initial modulus, the loading was stopped. The slope of the line connecting the initial modulus of the fatigue curve and the modulus after stopping loading at the intermittent time of 0s and the intermittent time of 3s was calculated respectively, and the ratio of the two was used as the evaluation index. The results are shown in Table 2 below. As can be seen from Table 2, with the increase of the dosage of the double-layer composite microcapsules, the self-healing index of the asphalt increased significantly. Compared with the ordinary 70# matrix asphalt, the healing index increased by 8.1% to 26.3%, indicating that its self-healing performance was enhanced.
[0073] Table 2 Healing index of asphalt prepared by double-layer composite microcapsules of Example 1
[0074] Asphalt Type Healing Index Ordinary 70# base asphalt 143.5 Microcapsule dosage 3% 155.1 Microcapsule dosage 4% 168.6 Microcapsule dosage 5% 181.2
[0075] The low-temperature crack resistance of the road surface layer asphalt containing double-layer composite microcapsules was tested, and the low-temperature crack resistance of the double-layer composite microcapsule asphalt containing different dosages (0%, 3%, 4%, 5%) was analyzed based on the penetration, softening point and ductility tests. The results are shown in Table 3 below. As can be seen from Table 3, with the increase in the dosage of double-layer composite microcapsules, the asphalt penetration increases, the softening point decreases, and the ductility increases. Compared with ordinary 70# matrix asphalt, its 25°C penetration increases by 6.5% to 17.5%, the softening point decreases by 1.9% to 8.4%, and the ductility increases by 12.2% to 23.6%, which shows that the double-layer composite microcapsules enhance the low-temperature crack resistance of asphalt.
[0076] Table 3 Low temperature crack resistance of asphalt prepared by double-layer composite microcapsules of Example 1
[0077]
[0078] The double-layer composite microcapsules suitable for asphalt surface layers of the present invention have both self-repairing, high energy storage and ice and snow resistance. The shell wall is prepared by using a double polymer, which can significantly improve the single response to the external environment of the single polymer shell material, and significantly improve the responsiveness of the microcapsules to the external environment and the release efficiency of the microcapsule core material; the methylated hexahydroxymethylmelamine resin has good environmental protection and safety due to its high cross-linking density and low formaldehyde content, and can also increase its reactivity and hydrophilicity, improve its wrapping of the core material, and enhance the stability of the core material; in addition, the methylated hexahydroxymethylmelamine resin has a good physical barrier effect, which can regulate the Release ability, thereby significantly improving the stability and functionality of the microcapsules; at the same time, the use of polyvinyl alcohol can be used as a vulnerable part of the external self-repairing microcapsule shell material, which is more susceptible to damage and can significantly improve the release ability of the core material; in addition, the use of carbon nanotubes can improve the thermal stability of the microcapsules and give the microcapsules conductive properties. Carbon nanotubes as photothermal materials can convert light energy into thermal energy to improve the energy storage effect of phase change materials. Carbon nanotubes generate heat energy under the action of external electric or magnetic fields to further improve the energy storage of phase change materials. In addition, carbon nanotubes can increase the filling effect of the core material on cracks and pores, improve the permeability and repairability of the core material, and improve the self-healing performance of the material. The double-layer composite microcapsules of the present invention, which are suitable for asphalt surface layers and have both self-repairing, high energy storage and ice and snow resistance, can achieve a high survival rate of microcapsules and a high healing repair rate of asphalt pavement cracks under the synergistic effect of each layer of materials, and can alleviate the problems of low thermal conductivity and easy leakage of phase change materials. The heat and high energy storage generated will increase the temperature of the asphalt material, melt the ice and snow on the asphalt pavement and inhibit the formation of ice layers, ultimately realizing the self-repairing-high energy storage-long-term ice and snow resistance mechanism.
Claims
1. A double-layer composite microcapsule with self-repairing, high energy storage and ice and snow resistance suitable for asphalt surface layer, characterized in that: The double-layer composite microcapsule is composed of an inner phase-change microcapsule core, an inner phase-change microcapsule shell, an outer self-repairing microcapsule core and an outer self-repairing microcapsule shell from the inside to the outside. The internal phase change microcapsule core is a mixture of octanoic acid, tetradecane, sodium polyacrylate emulsifier and deionized water; the internal phase change microcapsule shell is a mixture of carbon nanotubes, a double polymer and deionized water, wherein the double polymer is prepared from polyvinyl alcohol and methyl etherified hexamethylol melamine resin; The core of the external self-repairing microcapsule is mixed with bio-oil, carbon nanotubes, styrene maleic anhydride emulsifier, polyether F127 surfactant and deionized water; the shell of the external self-repairing microcapsule is mixed with carbon nanotubes, a double polymer and deionized water, wherein the double polymer is prepared from polyvinyl alcohol and methylated hexahydroxymethyl melamine resin.
2. A method for preparing a double-layer composite microcapsule with self-repairing, high energy storage and ice and snow resistance suitable for asphalt surface layer as claimed in claim 1, characterized in that: The method proceeds as follows:
1. Preparation of internal phase change microcapsule core solution: Weigh sodium polyacrylate emulsifier, octanoic acid, tetradecane and deionized water in a mass ratio of 1: (95-100): (95-100): (190-210) respectively; first mix octanoic acid and tetradecane, then add them into deionized water and mix evenly, and heat until the raw materials are completely dissolved to obtain a mixed solution; then adjust the pH value of the mixed solution to 3.5-4.5 with 1-1.5 mol / L citric acid; finally, add sodium polyacrylate emulsifier to the mixed solution, stir for 20-40 min at a temperature of 65-75° C. for emulsification, and obtain a uniform and stable internal phase change microcapsule core solution; 2. Preparation of internal phase change microcapsule shell solution: Weigh polyvinyl alcohol, methyl etherified hexahydroxymethyl melamine resin, carbon nanotubes and deionized water according to the mass ratio of 1: (65-70): (1.2-1.5): (140-155); add polyvinyl alcohol to deionized water and mix well, then add methyl etherified hexahydroxymethyl melamine resin and mix well to obtain a mixed solution; adjust the pH value of the mixed solution to 7.5-8.5 with sodium hydroxide solution, and then stir for 20-40 minutes at a temperature of 65-75°C and a stirring speed of 500-700 r / min; finally, add carbon nanotubes to the mixed solution, and treat it ultrasonically to entangle it with the double polymer and mix well to obtain an internal phase change microcapsule shell solution; 3. Preparation of internal high energy storage phase change microcapsules: drip the internal phase change microcapsule shell solution into the internal phase change microcapsule core solution, and adjust the solution pH to 3.5-4.5 with citric acid; after dripping the internal phase change microcapsule shell solution, stir at a temperature of 65-75°C and a stirring speed of 1000-1500r / min for 60-90min to allow the inner wall material to undergo a cross-linking and curing reaction on the surface of the core material, and stop stirring after the solution temperature is naturally cooled to room temperature; then filter the reaction solution, wash with anhydrous ethanol, and vacuum dry to obtain internal high energy storage phase change microcapsules; 4. Preparation of external self-healing microcapsule core solution: According to the mass ratio of 1: (1.5-2): (2-3): (85-95): (185-200), respectively take polyether F127 surfactant, carbon nanotubes, styrene maleic anhydride emulsifier, bio-oil and deionized water with a concentration of 15-20 g / L; first swell the styrene maleic anhydride emulsifier in deionized water for 20-24 hours, heat the expanded styrene maleic anhydride solution to 45-55°C, and then add sodium hydroxide solution to adjust the pH of the solution to 9.5-10.5; then add bio-oil, carbon nanotubes, and polyether F127 surfactant to the styrene maleic anhydride solution, and stir with a high-speed shearing machine at a stirring speed of 500-700 r / min for 25-35 minutes to obtain a stable and uniform external self-healing microcapsule core solution; 5. Preparation of external self-repairing microcapsule shell solution: polyvinyl alcohol, methyl etherified hexahydroxymethyl melamine resin, carbon nanotubes and deionized water are taken respectively in a mass ratio of 1: (65-70): (1.2-1.5): (140-155); polyvinyl alcohol and deionized water are stirred evenly, and added to the methyl etherified hexahydroxymethyl melamine resin, stirred evenly to obtain a mixed solution; the pH value of the mixed solution is adjusted to 7.5-8.5 with sodium hydroxide solution; then stirred at a temperature of 65-75°C and a stirring speed of 500-700r / min for 20-40min; finally, carbon nanotubes are added, and after ultrasonic treatment, they are entangled with the double polymer and mixed evenly to obtain an external microcapsule shell solution; 6. Preparation of double-layer composite microcapsules: Add the inner high energy storage phase change microcapsules to the outer self-repairing microcapsule core solution at a temperature of 20-30°C, and then add them dropwise to the outer self-repairing microcapsule shell solution. The outer self-repairing microcapsule core material containing the inner high energy storage phase change microcapsules attracts the outer wall material to the surrounding through electrostatic adsorption; After the external self-repairing microcapsule shell solution is added, the temperature is increased at a rate of 1 to 5°C / min. When the solution temperature reaches 65°C, citric acid solution is added to adjust the solution pH value to 4 to 5. The temperature is continued to be increased at a rate of 1 to 5°C / min until the solution temperature reaches 80°C and stirred at this temperature at a stirring speed of 1000 to 1500 r / min for 60 to 90 minutes. The outer wall material undergoes a cross-linking and curing reaction on the surface of the core material through mechanical stirring. The solution temperature is naturally cooled to room temperature and stirring is stopped. Finally, the reaction solution is filtered, washed with anhydrous ethanol, and vacuum dried to obtain a double-layer composite microcapsule suitable for the asphalt surface layer that has both self-repairing, high energy storage and ice and snow resistance.
3. The method for preparing a double-layer composite microcapsule with self-repairing, high energy storage and ice and snow resistance suitable for asphalt surface layer according to claim 2, characterized in that: The ultrasonic treatment described in step 2 is performed using a cell crusher, with an ultrasonic power of 85 to 95 W, an amplitude of 50% to 60%, and a time of 60 to 90 min.
4. The method for preparing a double-layer composite microcapsule with self-repairing, high energy storage and ice and snow resistance suitable for asphalt surface layer according to claim 2 or 3, characterized in that: In step three, the mass ratio of the internal phase change microcapsule shell solution to the internal phase change microcapsule core solution is 1:(1.4-1.6).
5. The method for preparing a double-layer composite microcapsule with self-repairing, high energy storage and ice and snow resistance suitable for asphalt surface layer according to claim 2 or 3, characterized in that: The concentration of the citric acid solution in step 3 and step 6 is 1-1.5 mol / L.
6. The method for preparing a double-layer composite microcapsule with self-repairing, high energy storage and ice and snow resistance suitable for asphalt surface layer according to claim 2 or 3, characterized in that: The concentration of the sodium hydroxide solution in step 2, step 4 and step 5 is 1-2 mol / L.
7. The method for preparing a double-layer composite microcapsule with self-repairing, high energy storage and ice and snow resistance suitable for asphalt surface layer according to claim 2 or 3, characterized in that: The ultrasonic treatment in step 5 is performed using a cell crusher, and the ultrasonic power is 85-95 W, the amplitude is 50%-60%, and the time is 60-90 min.
8. The method for preparing a double-layer composite microcapsule with self-repairing, high energy storage and ice and snow resistance suitable for asphalt surface layer according to claim 2 or 3, characterized in that: The mass ratio of the external self-repairing microcapsule shell solution to the external self-repairing microcapsule core solution described in step six is 1:(1.4-1.6).
9. The use of a double-layer composite microcapsule with self-repairing, high energy storage and ice and snow resistance suitable for asphalt surface layer as claimed in claim 1, characterized in that The application is to apply double-layer composite microcapsules to the surface layer of asphalt pavement.
10. The use of a double-layer composite microcapsule with self-repairing, high energy storage and ice and snow resistance suitable for asphalt surface layer according to claim 9, characterized in that: The method for preparing highway surface layer asphalt using double-layer composite microcapsules is carried out according to the following steps: adding double-layer composite microcapsules suitable for the asphalt surface layer and having both self-repairing, high energy storage and ice and snow resistance to the asphalt in a molten state, stirring for 30 to 45 minutes under the condition that the stirring speed of the mechanical device is 200 to 300 r / min; finally, keeping at the melting temperature of the asphalt for 10 to 15 minutes to obtain the highway surface layer asphalt prepared by the double-layer composite microcapsules; wherein the added mass of the double-layer composite microcapsules is 3% to 5% of the mass of the asphalt.
Citation Information
Patent Citations
Method for preparing organic / inorganic composite double-layer wall material high-thermal resistance microcapsule for selfreparing of pitch
CN107400373A
Asphalt material based on phase change capsule and preparation process thereof
CN113861704A
Preparation method of self-temperature-adjusting asphalt pavement change microcapsule in large-temperature-difference region
CN115322752A
Self-healing asphalt by rejuvenator-containing microcapsules activatable at will by irradiation
WO2020173923A1
Cited By
Double-layer composite microcapsule with self-repairing, high energy storage and ice and snow resistance as well as preparation method and application of double-layer composite microcapsule
CN119752237A
A double-layer composite microcapsule with self-repairing, high energy storage and ice and snow resistance, as well as its preparation method and application
CN119752237B
High-wear-resistance self-repairing composite floor coating and preparation process thereof
CN120399543A
Reusable fire barrier and preparation method thereof
CN120698770A